Religious Justification and Gendered Subjugation: Narrative Polygamy Through Banjar Women's - Prayogo, Agung; Husin, Husin; Fajeri, Samsul (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study explores the voices of Banjar migrant women who experienced polygamy, focusing on their lived experiences and the socio-cultural mechanisms that legitimize this practice. Employing a life history method, the research draws on in-depth interviews with Banjar women subjected to polygamous marriages in Serdang Bedagai, Indonesia. Data were analyzed through a systematic process involving data reduction, narrative presentation, and conclusion drawing. The findings reveal that polygamy within Banjar society is deeply embedded in religious interpretations, cultural traditions, and social norms, all of which are reinforced by the authority of Tuan Guru (religious leaders) who frame the role of polygamous wives as spiritually honorable. However, beneath this constructed legitimacy lies a system of male domination that operates through three interrelated forms of power: material power, manifested in male control over economic resources; symbolic power, which enhances male social status through polygamy; and normative power, which restricts women’s resistance through religious and cultural justification. Together, these forms of power constitute a cohesive structure of gendered subjugation, wherein polygamy functions not only as a personal or cultural practice but as an institutionalized mechanism of oppression.